Corneal endothelial cell coating during phacoemulsification using a new dispersive hyaluronic acid ophthalmic viscosurgical device - Kretz, Florian Tobias Alwin; Limberger, Il-Joo; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2014)
Purpose - To compare the corneal endothelial coating of a new hyaluronic acid ophthalmic viscosurgical device (OVD) with dispersive properties with that of a standard hyaluronic acid OVD with cohesive properties. - Setting - David J. Apple International Laboratory for Ocular Pathology, Department of Ophthalmology, University of Heidelberg, Germany. - Design - Experimental study. - Methods - The corneal endothelial cell coating of a new dispersive OVD (sodium hyaluronate 3% [Healon Endocoat]) and a standard cohesive hyaluronic acid OVD (sodium hyaluronate 1.4% [Healon GV]) as well as their combination using the soft-shell technique were evaluated. All OVDs were stained with fluorescein. Each of the 3 test groups comprised 10 porcine eyes. Cataract surgery was performed with identical phacoemulsification settings and time frames. Afterward, the cornea was trephined and a photograph taken of the endothelial side under blue light. The corneal coating with OVD was evaluated using planimetric image-analysis software. - Results - The least endothelial coating was in the cohesive group (71%), while the dispersive group had statistically significantly higher adherence to the endothelium (87%) (P=.0009). The greatest endothelial coating was in the soft-shell technique group (93%); however, the difference between that group and the dispersive group was not statistically significant (P=.0962). - Conclusion - The new dispersive hyaluronic acid OVD with a low molecular weight showed a greater adherence to the endothelial surface than the standard cohesive hyaluronic acid OVD with a higher molecular weight. - Financial Disclosure - No author has a financial or proprietary interest in any material or method mentioned.
Gesehen am 22.09.2020